Core outcome set for research studies evaluating treatments for twin–twin transfusion syndrome. (11th July 2019) - Perry, H.; Duffy, J. M. N.; Reed, K.; Baschat, A.; Deprest, J.; Hecher, K.; Lewi, L.; Lopriore, E.; Oepkes, D.; Khalil, A.; ,
ABSTRACT: Objective: To develop, using a Delphi procedure and a nominal group technique, a core outcome set (COS) for studies evaluating treatments for twin–twin transfusion syndrome (TTTS), which should assist in standardizing outcome selection, collection and reporting in future research studies. Methods: An international steering group comprising healthcare professionals, researchers and patients with experience of TTTS guided the development of this COS. Potential core outcomes, identified through a comprehensive literature review and supplemented by outcomes suggested by the steering group, were entered into a three‐round Delphi survey. Healthcare professionals, researchers, and patients or relatives of patients who had experienced TTTS were invited to participate. Consensus was defined a priori using the 15%/70% definition of the Core Outcome Measures in Effectiveness Trials (COMET) initiative. The modified nominal group technique was used to evaluate the consensus outcomes in a face‐to‐face consultation meeting and identify the final COS. Results: One hundred and three participants, from 29 countries, participated in the three‐round Delphi survey. Of those, 88 completed all three rounds. Twenty‐two consensus outcomes were identified through the Delphi procedure and entered into the modified nominal group technique. The consensus meeting was attended by 11 healthcare professionals, two researchers and three patients; 12 core outcomes were prioritized for inclusion in the COS. Fetal core outcomes included live birth, pregnancy loss (including miscarriage, stillbirth, termination of pregnancy and neonatal mortality), subsequent death of a cotwin following single‐twin demise at the time of treatment, recurrence of TTTS, twin anemia–polycythemia sequence and amniotic band syndrome. Neonatal core outcomes included gestational age at delivery, birth weight, brain injury syndromes and ischemic limb injury. Maternal core outcomes included maternal mortality and admission to Level‐2 or ‐3 care setting. One aspirational outcome, neurodevelopment at 18–24 months of age, was also prioritized. Conclusions: Implementing the COS for TTTS within future research studies could make a substantial contribution to advancing the usefulness of research in TTTS. Standardized definitions and measurement instruments are now required for individual core outcomes. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.